Web based Approach to overcome the Market Information Gap between poultry farmers and potential buyers in Tanzania. - Mambile, Cesilia; Machuve, Dina (My University, 2018)
Poultry farming is very important sector in Tanzania because it improves the human health and when sold provides income, it supports the livelihoods of 3.7 million households in Tanzania. Poultry farming sector is facing a challenge of lack of market information, also absence of well-coordinated system which is harmonized between stakeholders. Both poultry farmers and buyers rely on informal market information. The findings form this study shows that key market information required by poultry farmers and buyers are price, buyer or farmer location, Poultry kilograms, amount of poultry needed by buyers, amount of poultry products needed by buyers, types of poultry needed by buyers and kind of poultry products needed by buyers. This paper discusses this key market information required by poultry farmers and buyers, also the challenges faced due to lack of market information. In order to disseminate the identified market information requirements and to overcome the mentioned challenges the web based platform has been proposed as a solution to overcome the market information gap.
Supplemental Materials: https://osf.io/acjfe/
Keywords: Market Information; Poultry and Poultry Products; Poultry Farmers and Buyers; Web Based Application